Profitability (ROA), Solvency (DER), Company Size, and Public Accounting Firm Reputation on Audit Delay in Sharia Manufacturing Companies on the IDX (2020–2025) - Hariyanto, Totok; Risnaini, Umi Suswati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose of this study is to examine and analyze the effect of profitability, solvency, company size, and the reputation of public accounting firms on audit delay in sharia manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2025. Profitability as measured by ROA has an effect on audit delay, solvency as measured by DER has an effect on audit delay, the effect of company size as measured by size has an effect on audit delay, and the effect of public accounting firm reputation as measured by dummy variables has an effect on audit delay. The data analysis technique in this study is multiple linear regression using eviews. The sampling method is the Solvin formula, with a sample size of 75 companies that have met the sampling criteria. Based on the analysis, it can be concluded that the variables of profitability, solvency, company size, and public accounting firm reputation partially and simultaneously have an effect on audit delay.